Formação continuada e desenvolvimento profissional do tradutor e intérprete de língua de sinais na Educação a Distância (EaD) - Giamlourenço, Priscila Regina Gonçalves de Melo (Universidade Federal de São Carlos, 2021)
The sign language translator and interpreter, TILS , into the context of federal high education institutions, IFES , work on educational processes that are aimed to deaf students within inclusion projects, working this way as educational agente on teaching, resarch and extension activities. Then, considering the plurality of knowledge to the practice, and the demand for training, this study aims to investigate training needs of TILS that work in IFES, seeking to organize a training course for TILS in a virtual platform, promoting that training from a perspective that enables a teaching and learning relationship that take into account the role of the another one on it, and analyses this proposal´s process. Through an intervention-research, it was carried out a continuous training by distance education modality, which democratize professional training offering, and favors the collective construction of knowledge. The course Libras’ translator and interpreter: practice and professional training was offered by General Secretariat of Distance Education, SEaD, of UFSCar. The survey participants were four TILS that worked in IFES from different regions of Brazil, and data were collected from the forums of discussion. The analyses allowed find three Dimensions of training needs, Specific, Educational and Professional, which are interdependents and constituted from interrelated knowledges. The Specific Dimension is constituted from linguistic-cultural, discursive and technical knowledges, which are related to linguistics, grammatical and cultural factors related to the public with whom TILS work in different modalities and directions of the translation process in face-to-face meetings or mediated by Technologies. Educational Dimension is constituted from political-educational, didactic-pedagogical, and institutional knowledges, which are related to teaching levels, organization and the structure of the context of work, its educational processes premisses and its social relations. Professional Dimension is constituted from characteristic, methodological and social knowledges of the area of translation and interpretation in deafness field, which corresponds to acting, knowledge and knowledge production spheres. It is understood the importance of public policies focused on TILS training. While this advance is underway, the intervention-research in individual and shared reflection processes for the construction of knowledge could favor the approximation of professionals and researchers to design actions that promote conditions offering continuous education. An institutional training program in free distance education, directed to the training of professionals that work with deaf students in different levels, modalities and teaching contexts, due to the protagonism of these professionals, and the intervention of professor and researches, is presented as an alternative, since the modality favors exchange, reflections, and even new practices adopted by TILS from different geographic reality, making it possible to develop professional training projects incorporated into daily life, and connected to service training experiences to systematize and reframe the practice. Whithin its possibilities, the research sought to contribute to scientific knowledge and conditions for offering professional training through free access modality, bringing a return to the field of translation and interpretation in the context of deafness in dialogue and with the subsidy of Pedagogy, Educational Psychology, and Distance Education as fields of training, profession and work performance.
Continuing training and professional development of sign language translator and interpreter in distance education (EaD)
Keywords: TILS; Formação continuada; EaD; Sing language translator and interpreter; Continuous training; Distance education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO